FAMILY MEDICINE — THE OPTIMAL APPROACH TO PREVENTION OF CARDIOVASCULAR AND OTHER NON-COMMUNICABLE DISEASES - N. V. Suslonova; R. G. Oganov; N. N. Shevtsova (Кардиоваскулярная терапия и профилактика)
.